Aggressive angiomyxoma of the vulva: An uncommon entity - Mahendra M Kura; Saurabh R Jindal; Usha N Khemani (Wolters Kluwer Medknow Publications, 2012)
Aggressive angiomyxoma is a rare, locally invasive mesenchymal tumor occurring usually in women of reproductive age, which carries a high risk for local relapse; hence the need to differentiate it from the other mesenchymal tumors occurring in this region. We describe a case of a 44-year-old female presenting with a large pedunculated swelling on the right labia majora.